Nursing with integrity and excellence is possible - García García, Andrea Bibiana (Investigación y Educación en Enfermería, 2008)
A 5 term student of nursing follows her teacher caring children and teenagers. She admires her as paradigm for her efficiency, neatness, commitment and particular warmth towards smaller children. All this impresses the student who therefore reflects on the practice on infirmary, ethics, society and the times we live in, to conclude that we all have the responsibility to optimize each own’s practice, banning for good mediocrity and conformism, in the every day struggle for scientific and ethical excellence.